2017
DOI: 10.1111/fog.12227
|View full text |Cite
|
Sign up to set email alerts
|

Effects of environmental variables on survey catch rates and distribution by size of shallow‐ and deep‐water Cape hakes, Merluccius capensis and Merluccius paradoxus off Namibia

Abstract: In order to study the effects of temperature, oxygen, salinity and time of day on survey trawl catches, we modeled observed catches of juvenile, small, medium and large hakes per station as functions of zenith angle of the sun, geographical position, year, temperature, salinity, oxygen and depth. We used data from summer demersal surveys conducted during the period 2002–2015, together with a computation of the corresponding light level data from which the solar zenith angles were obtained, and fitted the gener… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
19
1
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(24 citation statements)
references
References 33 publications
(67 reference statements)
2
19
1
2
Order By: Relevance
“…Small M. paradoxus were associated with environmental oxygen ranges that are restricted, indicating that their presence was likely associated with hypoxic conditions (<2 ml O 2 l -1 ) (Monteiro and van der Plas 2006), although the small fish mostly inhabited oxygen-depleted water (2-3 ml O 2 l -1 ) and appeared to occur less often in waters with high oxygen concentrations (>3 ml O 2 l -1 ). In an analysis of the catch rates of both hake species, Kainge et al (2017) found that oxygen was not an important covariate. Singh and Lamont (2016) found that M. paradoxus juveniles mostly occurred in moderately oxygenated water (2-3.5 ml O 2 l -1 ).…”
Section: Environmental Niche Of Merluccius Paradoxusmentioning
confidence: 95%
See 2 more Smart Citations
“…Small M. paradoxus were associated with environmental oxygen ranges that are restricted, indicating that their presence was likely associated with hypoxic conditions (<2 ml O 2 l -1 ) (Monteiro and van der Plas 2006), although the small fish mostly inhabited oxygen-depleted water (2-3 ml O 2 l -1 ) and appeared to occur less often in waters with high oxygen concentrations (>3 ml O 2 l -1 ). In an analysis of the catch rates of both hake species, Kainge et al (2017) found that oxygen was not an important covariate. Singh and Lamont (2016) found that M. paradoxus juveniles mostly occurred in moderately oxygenated water (2-3.5 ml O 2 l -1 ).…”
Section: Environmental Niche Of Merluccius Paradoxusmentioning
confidence: 95%
“…Singh and Lamont (2016) mostly found M. paradoxus juveniles in moderately oxygenated waters (2-3.5 ml O 2 l -1 ) and it appeared that temperature was more important than oxygen in determining the distributions of M. paradoxus juveniles. Kainge et al (2017) found that juveniles of M. capensis were more sensitive than juveniles of M. paradoxus to dissolved oxygen concentrations.…”
Section: Introductionmentioning
confidence: 95%
See 1 more Smart Citation
“…• Decreased pelagic fish catches off Angola from the late 1970's to 1990's, with recoveries since the mid-2000's (Kainge et al, 2020). Oxygen has been shown to be a key determinant of species such as juvenile deepwater hake in the Northern Benguela (Kainge et al, 2017) and the climatologies document warmer temperature and higher oxygen levels, coinciding with the recovery of fisheries.…”
Section: Biogeographic Zone Boundaries In Comparison To Key Climatological Map Featuresmentioning
confidence: 99%
“…The African continental shelf is host to natural resources of particular and critical socio-economic value for coastal communities (Kainge et al, 2020). Understanding the significance of observed changes in ocean variables such as temperature and wind (Roualt et al, 2010;Leduc et al, 2010;Santos et al, 2012;Beal et al, 2016;Vizy et al, 2018;Malan et al, 2019), and ecosystem changes such as species range shifts and variability in species abundance (Cockcroft et al, 2008;Roy et al, 2007;Coetzee et al, 2008;Yemane et al, 2014;Blamey et al, 2015;Jarre et al, 2015a;Van der Linge et al, 2016;Kainge et al, 2017;Van der Linge and Hampton, 2018), have transdisciplinary significance (Potts et al, 2014;Augustyn et al, 2017;Hobday and Pecl, 2014;Kainge et al, 2020). Construction of climatological maps of key ocean variables, based on the calculation of mean fields from historical data sets, are valuable reference tools in this regard.…”
Section: Introductionmentioning
confidence: 99%